Candidate fodder species for goat production in Northern Ghana - Partey, Samuel T.; Avornyo, Franklin K.; Ouédraogo, Mathieu; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Livestock production employs over 60% of rural house-holds in the three northern regions of Ghana, making in-vestment in this industry critical for alleviating poverty and enhancing food security. Among other factors, the Ministry of Food and Agriculture reports access to sustainable feed supply as one of the livestock industry’s key constraints. As most livestock are kept on a free-range system, forage of fair nutritive value is normally scarce in the dry season due to recurrent droughts, continuous over-grazing and lack of range improvement interventions. Often, palatable and productive perennial grasses, legumes and herbs be-come replaced with unpalatable, low quality annual spe-cies, with a concomitant loss of soil fertility. The nutritive value of available pasture species is therefore often poor with low levels of crude protein. The predominant small scale, subsistence livestock producers are also challenged with the financial resources to afford a continuous supple-mentation of concentrate feeds to their animals. Recent re-search has been directed to using tree leaves as fodder for livestock due to many advantages such as supply of good quality green fodder even in the dry season as well as high crude protein and minerals contents. In the Lawra and Jirapa Districts of the Upper West Region of Ghana, the CGIAR Research Program on Climate Change and Agriculture (CCAFS) established a Climate-Smart Village (CSV), an agriculture research for develop-ment site where various agricultural innovations are tested on their potential to deliver on any of the 3 pillars (produc-tivity, adaptation and mitigation) of climate-smart agricul-ture (CSA). Among many CSA options at the CSV, the in-tegration of multipurpose trees on farmlands is promoted as a CSA practice for improving fodder availability, increas-ing overall farm productivity, improving ecological resili-ence and providing farmers with important safety net op-portunities against climate-related risks. In this study, we used a participatory approach to document and character-ize fodder trees and shrubs that are prioritized by farmers for livestock production. Documentation of fodder species was based on question-naire interviews, focus group discussions and desktop re-views. Top fodder species selected by farmers were char-acterized for the nutritional composition and intake by farmer preferred livestock.